Kreativitas Siswa Melalui Kegiatan Bermain Tradisiaonal Raba-Raba Dalam Meningkatkan Kemampuan Sosial Emosional Anak - Suriani Suriani; Hendra Hendra; Abdurrahman Abdurrahman (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to describe students’ creativity through the implementation of the traditional raba-raba game as an effort to improve children’s social-emotional abilities at Al-Mahasin Kindergarten in Bima. This research employed a qualitative approach with a case study design. The research subjects consisted of 15 Group B children aged 5–6 years, while the supporting informants included three teachers and five parents. Data were collected through participatory observation, semi-structured interviews, and documentation. The results of the study showed that children’s creativity appeared in three main aspects: the ability to choose hiding places, the ability to develop playing strategies, and the ability to express emotions and communicate during the activity. The implementation of the traditional raba-raba game was carried out through three stages, namely planning, implementation, and evaluation. The supporting factors for children’s creativity included children’s enthusiasm, the role of teachers, the condition of the play environment, and parental involvement. Meanwhile, the inhibiting factors included time constraints, differences in children’s characteristics, disturbances from the surrounding environment, and gadget use. Therefore, the traditional raba-raba game has proven to be effective as a medium for developing creativity and social-emotional abilities in early childhood in an integrated manner.